Surface Sensing for Biofilm Formation in Pseudomonas aeruginosa - Chang, Chien-Yi (Frontiers in Microbiology, 2018)
Bacterial cells aggregating and forming biofilms on biotic or abiotic surfaces is a ubiquitous bacterial behavior under various conditions. In clinical settings, persistent presence of biofilms increases risk in healthcare-associated infections and causes huge healthcare and economic burdens. Bacteria within biofilms are protected from external damages and the attack from host immune systems and able to exchange genomic information including antibiotic-resistant genes. Dispersed bacterial cells from biofilms which attach to medical devices or host tissues may also be the origin of further infections. Understanding how bacteria develop biofilms would be pertinent in tackling biofilm-associated infections and transmission. Biofilms have been suggested as a continuum of growth modes for adapting to different environments initiating from bacterial cells sensing attachment on a surface and then switching bacterial physiological status for mature biofilm development. It is crucial to understand bacterial gene regulatory networks and decision-making process for biofilm formation upon initial surface attachment. Pseudomonas aeruginosa is one of the model microorganisms for studying bacterial population behaviours. Several hypothesis and studies suggested that the extracellular macromolecules and appendages play important roles for bacterial responding to the surface attachment. Here I review recent studies on potential molecular mechanisms and signal transduction pathways for P. aeruginosa surface sensing.